Innovation in Space - Desmet, Klaus; Rossi-Hansberg, Esteban (American Economic Review, 2012)
This paper shows how competition for land may lead firms to optimally innovate in spite of the market being perfectly competitive. When bidding for a location, firms can enhance their bid by investing in innovations that make the land more valuable. Firms are willing to innovate because the non-replicability of land implies that they will not be undercut by some other producer leading to losses as in the standard theory. In the absence of spillovers over space and over time, firms will optimally innovate. Empirical evidence from U.S. metropolitan areas supports the predictions of the theory.